The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/14651858.cd004517.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for depression

Abstract: Findings of the present meta-analysis indicate that music therapy provides short-term beneficial effects for people with depression. Music therapy added to treatment as usual (TAU) seems to improve depressive symptoms compared with TAU alone. Additionally, music therapy plus TAU is not associated with more or fewer adverse events than TAU alone. Music therapy also shows efficacy in decreasing anxiety levels and improving functioning of depressed individuals.Future trials based on adequate design and larger sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
274
1
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 400 publications
(297 citation statements)
references
References 73 publications
8
274
1
14
Order By: Relevance
“…When considering these results in terms of their clinical significance, around 38.2% -64.7% of the participants experienced a meaningful improvement in mental wellbeing, whereas only 0% -11.8% of the participants experienced a meaningful decline. These findings are consistent with a broader range of studies which have found growing support for music and arts interventions improving mental health and wellbeing in participants with mental health conditions (Aalbers et al, 2017;Geretsegger et al, 2017;Stickley, Wright & Slade, 2018;Van Lith, Schofield, & Fenner, 2013). However, to our knowledge there is no other research which explicitly evaluates the impact of partaking in creative writing groups on the mental wellbeing of people with mental health conditions.…”
Section: Arts-based Groups For Mental Health Recoverysupporting
confidence: 89%
See 4 more Smart Citations
“…When considering these results in terms of their clinical significance, around 38.2% -64.7% of the participants experienced a meaningful improvement in mental wellbeing, whereas only 0% -11.8% of the participants experienced a meaningful decline. These findings are consistent with a broader range of studies which have found growing support for music and arts interventions improving mental health and wellbeing in participants with mental health conditions (Aalbers et al, 2017;Geretsegger et al, 2017;Stickley, Wright & Slade, 2018;Van Lith, Schofield, & Fenner, 2013). However, to our knowledge there is no other research which explicitly evaluates the impact of partaking in creative writing groups on the mental wellbeing of people with mental health conditions.…”
Section: Arts-based Groups For Mental Health Recoverysupporting
confidence: 89%
“…In clinical mental health settings, the therapeutic use of music has typically been undertaken as music therapy, defined as "the clinical and evidence-based use of music interventions to accomplish individualised goals within a therapeutic relationship by a credentialed professional who has completed an approved music therapy program" (American Music Therapy Association, 2018). Recent reviews indicate that music therapy can enhance treatment outcomes of people with depression (Aalbers et al, 2017), schizophrenia (Geretsegger et al, 2017), and severe mental health conditions (Gold, Solli, Krüger, & Lie, 2009). However, increasingly music activities, such as choirs, are being used to engage people experiencing mental health conditions in non-clinical contexts with musicians who are not necessarily trained in music therapy (McNaughton, White & Stacy, 2005).…”
Section: Choir Singingmentioning
confidence: 99%
See 3 more Smart Citations